The Effect of Implementing the Problem Based Learning Model Integrated with Reading, Mind Mapping, and Sharing on Creative Thinking Skills and Learning Motivation of Class XI Science Students - Nur Khafifah; Mushawwir Teiyeb; Rachmawaty; Firdaus Daud; Faisal (Postgraduate, University of Mataram, 2025)
The main focus of this study is to explore the effect of implementing the Problem Based Learning model integrated with reading, mind mapping and sharing on creative thinking skills and biology learning motivation of class XI IPA students at SMA Negeri 21 Makassar. The type of research used is quasi-experimental research with a quantitative approach. This research was conducted at SMA Negeri 21 Makassar with class XI IPA students as subjects. Samples were taken using a random method. From the results of data analysis, it was obtained that: Innovative thinking skills in the treatment group and comparison group during the pretest were classified as moderate or less than optimal and during the posttest there was an increase in creative thinking skills. The experimental group had a higher and more comprehensive level of biology learning motivation, while in the control group, namely the creative category; The control group's biology learning motivation was not yet comprehensive and limited; The results of the ANOVA test showed that Problem Based Learning integrated with reading, mind mapping, and sharing strategies had an effect on students' creative thinking skills; The results of the ANOVA test showed that the Problem Based Learning model integrated with reading, mind mapping, and sharing had a significant effect on students' learning motivation; The results of the Manova analysis show that the Problem Based Learning model integrated with reading, mind mapping, and sharing has a simultaneous effect on students' creative thinking skills and learning motivation.